2002
DOI: 10.5483/bmbrep.2002.35.4.377
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Trioxide Induces Apoptosis in Chronic Myelogenous Leukemia K562 Cells:Possible Involvement of p38 MAP Kinase

Abstract: Arsenic trioxide (As 2 O 3 ) was recently demonstrated to be an effective inducer of apoptosis in patients with relapsed acute promyelocytic leukemia (APL) as well as in patients with APL in whom all-trans-retinoic acid and conventional chemotherapy failed. Chronic myelogenous leukemia cells are highly resistant to chemotherapeutic drugs. To determine if As 2 O 3 might be useful for the treatment of chronic myelogenous leukemia, we examined the ability of As 2 O 3 to induce apoptosis in K562 cells. In vitro cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 19 publications
(17 reference statements)
5
35
0
Order By: Relevance
“…45 However, ATO-induced apoptosis in HepG 2 cells was shown to be independent of MAP kinase signaling pathways. 46 Consistent to Shim's report, 26 here we showed that ATO at 1 mM slightly activated p38 but not JNK, while bortezomib activated both JNK and p38. More significantly, both JNK and p38 were greatly activated by combined treatment of bortezomib and ATO, suggesting possible contribution of these two kinases in their synergistic effect in term of apoptosis induction.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…45 However, ATO-induced apoptosis in HepG 2 cells was shown to be independent of MAP kinase signaling pathways. 46 Consistent to Shim's report, 26 here we showed that ATO at 1 mM slightly activated p38 but not JNK, while bortezomib activated both JNK and p38. More significantly, both JNK and p38 were greatly activated by combined treatment of bortezomib and ATO, suggesting possible contribution of these two kinases in their synergistic effect in term of apoptosis induction.…”
Section: Discussionsupporting
confidence: 80%
“…[35][36][37] ATO at 10 mM was also reported to induce the activation of p38 and JNK with the inhibition extracellular signal-regulated kinase (ERK). 26 Consequently, we tested potential effects of bortezomib or/and ATO on these two kinases in K562 cells. As shown in Figure 5, bortezomib (32 nM) induced JNK and p38 activations, while ATO (1 mM) only slightly activated p38, as evidenced by their phosphorylated levels.…”
Section: Ato Enhances Bortezomib-induced Activations Of Jnk and P38 Mmentioning
confidence: 99%
See 1 more Smart Citation
“…events for apoptosis [18]. It should be noted that arsenic trioxide activate a number of signaling pathways, such as MAPK, ERK and JNK or suppress certain signaling pathways [19,20]. The molecular details of the network of different signaling molecules to regulate cell differentiation need to be further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…30 At subtoxic or clinically achievable concentrations (0.5-2 M), however, the effectiveness of ATO in apoptotic induction appears to be significantly reduced, resulting in prolonged proapoptotic periods (eg, 7-10 days). 31 Accordingly, transcriptome changes depicted by CPP-SOM of the ATO-treated series may mainly reflect proapoptotic activities induced by a low dose of ATO.…”
Section: Apoptosis Induced By Atomentioning
confidence: 99%